New Challenges in The Area of Organization of Vocational Education and Cooperation of Schools with Employers After The 2017 Reform of The Polish Educational System - Insights from Quantitative Research - Emilia PALANKIEWICZ-MITRUT (Communications of International Proceedings, 2025)
Vocational education is essential for reducing unemployment and equipping young people with skills that align with the evolving labor market. However, in Poland, it has historically been perceived as less prestigious than general education. The 2017 reform of the Polish educational system aimed to enhance its quality and attractiveness, yet its effectiveness remains underexplored. There is a significant gap in the literature regarding the impact of this reform on the organization of vocational education and the cooperation between schools and employers. While previous studies have focused on earlier reforms, primarily in the area of general education, little empirical research has assessed whether these changes effectively address the needs of vocational education and its adaptation to labor market demands. This study seeks to fill that void. Using a quantitative research approach, this study surveyed 158 teachers, vocational instructors, and school principals across Poland. The research examined changes in vocational education organization, school-employer collaboration, and the preparedness of students for the labor market. The respondents provided insights into the reform’s effectiveness and highlighted areas requiring further improvement, including infrastructure, teaching equipment, and stronger employer involvement in training programs. The findings indicate that while the reform has increased cooperation between vocational schools and external entities, significant challenges remain. Schools still lack adequate resources and opportunities for practical training. The mandatory vocational exam received mixed responses, with some educators viewing it as a positive step, while others questioned its effectiveness in improving education quality. Strengthening partnerships with employers, investing in modern infrastructure, and adapting curricula to meet labor market demands are crucial steps toward improving vocational education in Poland. Addressing these challenges will foster a more dynamic and responsive vocational education system, better preparing students for future employment.
Keywords: vocational education; education organization and cooperation with employers; vocational schools; technical school